Specialized Discourses and Their Readerships - Banks, David; Di Martino, Emilia; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This volume studies the relationship between the writers of specialized text and their readers in a broad range of settings, including research, popularization and education. It offers younger researchers an insight into the targeting process, helping them consider the impact their work can have, and showing them how to achieve greater exposure. Further, it offers an invaluable reflective instrument for beginning and experienced researchers, drawing on a veritable treasure trove of their colleagues' experience. As such, it represents a way for researchers and students in linguistics and related disciplines to access issues from a different, insider perspective. Reader targeting has become a very sophisticated process, with authors often addressing their potential readers even in video. Compared to other forms of writing, academic writing stands out because authors are, in the majority of cases, also consumers of the same type of products, which makes themexcellent "targeters." .
Editors' Preface: Specialized Discourses and their Readerships: A Historical Sketch and an Introduction to the Papers -- Chapter 1: The Scientific Research Article Publication Process as a Macro-Genre: Outlining the Parameters of Successful and Unsuccessful Communication between the Writers and the Gatekeeping Readers -- Chapter 2: "Logically, We Quite Agree with the IARC": Negotiating Interpersonal Meaning in a Corpus of Scientific Texts -- Chapter 3: Recognising Voices: The 'Voice-holder' Aspect of ENGAGEMENt in Experts' Tweets on the Fukushima Nuclear Crisis -- Chapter 4: From Academic Discourse to the Construal of Scientific Cognition and Knowledge Structures -- Chapter 5: Motion and Locution: A Pragma-scientific Study of Wole Soyinka's Death and the King's Horseman and Keye Abiona's Even Kins are Guilty -- Chapter 6: "Tetanus? Who Cares about Tetanus?": Audience Engagement and Co-participation in Medical Blogs.
Keywords: Applied linguistics; Linguistics -- Methodology; Intercultural communication; Applied Linguistics; Research Methods in Language and Linguistics; Intercultural Communication